Assessment of Heavy Metal Accumulation in the Soils and Hazelnut Plant (Corylus avellena L.) from Black Sea Coastal Region of Turkey - OZKUTLU, FARUK; TURAN, METIN; KORKMAZ, KURSAT; MING HUANG, YUH (Asian Journal of Chemistry, 2010)
For decades, heavy metal contamination due to traffic activities on roadside soils and crops has been one of the major concerns in developed and developing countries. Pollution assessment is the key factor to protect the ecological function and agricultural sustainability of soils. In order to investigate the extent of heavy metal contamination of roadside soil and hazelnut plant, 6 sampling sites, which were situated along the 010-17 motorway from Unye to Gulyali (Turkey), were selected. Soil and leaf samples were collected from 0-10, 11-20, 21-30, 31-40, 41- 50, 51-100, 101-200 and 201-400 m altitudes for each of the sampling sites. Total and available heavy metal concentrations in soil and hazelnut leaves were determined using ICP-OES after digestion. The concentrations of Al, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb and Zn in total and available forms in the soil and plant leaves were decreased with the increase of altitude at different rates. This data can be used to distinguish between sources of pollutant (traffic activity, agricultural, natural activities). Hence it is clear from the results that Pb, Cd and Ni contamination of roadside soils was contributed mainly from traffic activities and Cu and Zn were mainly due to agricultural activities as evidenced by their distribution patterns and their enrichment factors (EF). The enrichment value for distinguishing the accumulation of elements in the lower altitude location from the traffic activities to agricultural activities and natural erosion is about 1.5. However, the concentrations of these elements in hazelnut leaves were negligible. The concentration of most determined elements in this study area are better related to soil total concentration is linear (Cd, Fe, Ni, Pb and Zn) or quadratic (Co and Cr) relationship to soil available concentration except Mn and Cu which are better related to the later form.